The Influence of Higher Moments of Earnings Distributions on Career Decisions - Flyer, Fredrick A. (Journal of Labor Economics, 1997)
A model where choice of occupation is sequential is applied to college graduates from the National Longitudinal Study of the High School Class of 1972 to investigate how higher moments of occupational earnings distributions influence initial field of work. Individual specific life‐cycle earnings projections that incorporate option values of occupational mobility are generated, and the relationship between these pay measures and choice of initial occupation is explored within a multinomial logit framework. The findings indicate a strong positive relationship between these earnings predictions and the likelihood that college graduates enter an occupation.